2023
DOI: 10.3102/0013189x221141409
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Poverty: How Measures of Socioeconomic Status Have Changed Over Time

Abstract: Socioeconomic status (SES) is a common measure used to gauge social, cultural, and financial capital in scientific literature. Over time, SES research has produced an extremely wide and inconsistently used variety of SES variables and components. This study will review research that estimates SES and will examine common components and trends from the inception of its measurement to present data. A systematic review protocol was used to gather literature related to SES, and a historical analysis was conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…For example, given the importance of gender diversity in autistic individuals (Walsh et al, 2018; Warrier et al, 2020), reporting only males or failing to specify whether studies report gender, gender identity, or sex is insufficient for broadly understanding findings. In addition, perceptions about SES as a construct have changed over time, with no one validated assessment of SES (Long & Renbarger, 2023). Thus, it is perhaps unsurprising that studies included in this review varied in metrics of SES; researchers have the challenge of deciding what indicators of SES are meaningful for their population and how to summarize them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, given the importance of gender diversity in autistic individuals (Walsh et al, 2018; Warrier et al, 2020), reporting only males or failing to specify whether studies report gender, gender identity, or sex is insufficient for broadly understanding findings. In addition, perceptions about SES as a construct have changed over time, with no one validated assessment of SES (Long & Renbarger, 2023). Thus, it is perhaps unsurprising that studies included in this review varied in metrics of SES; researchers have the challenge of deciding what indicators of SES are meaningful for their population and how to summarize them.…”
Section: Discussionmentioning
confidence: 99%
“…This lack of clarity in operationalizing SES in reporting guidelines is reflected in the research literature. A historical analysis revealed that although parental education, occupation, and income are persistently frequent measures of SES, earlier assessment of SES focused on social capital while more recent assessment considered cultural and economic capital (Long & Renbarger, 2023). In practical terms, assessing SES with one indicator is insufficient and may be misleading; a doctoral student may have low income but high educational attainment and access to opportunities.…”
Section: Sesmentioning
confidence: 99%
“…This study focused on the nuanced facets of individual perceptions of social capital in the domains of family, neighborhood, and school (Grilo et al, 2023;Hoolihan & Thomas, 2020;Long & Renbarger, 2023). To assess family social capital, participants answered the speci c item: "Do you feel that your family understands you and gives attention to you?"…”
Section: Social Capital Indicatorsmentioning
confidence: 99%
“…Representing a complex dimensional construct used to assess social, cultural, and financial capital, SES is often divided into material gains like income, and non-material gains such as education and occupation (Long & Renbarger, 2023). SES also encompasses subjective and individual experiences of social class (W. M. Liu et al, 2004), and cultural knowledge and abilities of marginalized minority groups that often go unrecognized (Yosso, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…As theorized by sociologist Pierre Bourdieu, SES is a complex dimensional construct used to assess social (connections), cultural (skills, knowledge and education), symbolic (prestige), and financial capital (Bourdieu, 2011). Within neuroscience, SES is often assessed by material gains like income, and non-material gains such as education and occupation (Long & Renbarger, 2023). This tradition has been critiqued and expanded to include subjective and individual experiences of social class (W. M. Liu et al, 2004), and cultural knowledge and abilities of marginalized minority groups that often go unrecognized (Yosso, 2005).…”
Section: Introductionmentioning
confidence: 99%